Islamic Culture Historical Approach (Study of The System for Selecting Leaders) - Saiful Ansori; Maghfiroh, Siti (Islamic Studies Journal, 2022)
This study aims to find out what is meant by Islamic history and culture. In addition, it is also to find out how the system of selecting leaders is viewed in terms of an Islamic cultural history approach. The research method that the author uses here uses a type of literature review research with a qualitative approach. While the analysis technique chosen is descriptive analysis. From the results of an in-depth analysis when discussing the history of Islamic culture, in the context of Indonesian citizens who are predominantly Muslim, the existing culture cannot be separated from the influence of the teachings of Islam itself. Islam is present in the midst of existing pluralism and forms a diverse culture. With this diverse culture, the state then has quite a big and complicated responsibility. Therefore, the state exists with laws and regulations to regulate, uphold culture and justice. So the role of the leader is very decisive to carry out this justice. To choose a fair leader certainly has a way or system. Currently, the presidential election system in Indonesia uses a threshold presidential system. This is regulated in Law no. 7 of 2017 concerning General Elections article 222. It explains the threshold that must be reached to become a candidate for leader. Based on these problems, the writer needs to conduct a study of what is meant by Islamic history and culture. Apart from that, it is related to the election system for leaders, how is the threshold for presidential and vice presidential candidates in Indonesia in terms of an Islamic cultural history approach. The results of this study indicate that the history of Islam was first sourced from the messengers of Allah, namely the Prophets and Apostles. Then in general it is all humans who produce culture by being given more perfect provisions compared to other creatures created by Allah. Specifically, the history of Islamic culture begins with the creations of the Prophet Muhammad. Through an Islamic cultural history approach, a civilization and social order within a country are then able to develop according to their respective contexts. Likewise, the constitutional system that is currently in progress is inseparable from the creation of ideas or concepts that have been implemented during the Islamic State era in Medina. Especially since the reign of Khulafaur Rhasyidin.